Wild Grape-Associated Yeasts as Promising Biocontrol Agents against Vitis vinifera Fungal Pathogens - Cordero-Bueso, Gustavo; Mangieri, Nicola; Maghradze, David; Foschino, Roberto; Valdetara, Federica; Cantoral, Jesús M.; Vigentini, Ileana (Frontiers in Microbiology, 2017)
The increasing level of hazardous residues in the environment and food chains has led the European Union to restrict the use of chemical fungicides. Thus, exploiting new natural antagonistic microorganisms against fungal diseases could serve the agricultural production to reduce pre- and post-harvest losses, to boost safer practices for workers and to protect the consumers' health. The main aim of this work was to evaluate the antagonistic potential of epiphytic yeasts against Botrytis cinerea, Aspergillus carbonarius, and Penicillium expansum pathogen species. In particular, yeast isolation was carried out from grape berries of Vitis vinifera ssp sylvestris populations, of the Eurasian area, and V. vinifera ssp vinifera cultivars from three different farming systems (organic, biodynamic, and conventional). Strains able to inhibit or slow the growth of pathogens were selected by in vitro and in vivo experiments. The most effective antagonist yeast strains were subsequently assayed for their capability to colonize the grape berries. Finally, possible modes of action, such as nutrients and space competition, iron depletion, cell wall degrading enzymes, diffusible and volatile antimicrobial compounds, and biofilm formation, were investigated as well. Two hundred and thirty-one yeast strains belonging to 26 different species were isolated; 20 of them, ascribed to eight species, showed antagonistic action against all molds. Yeasts isolated from V. vinifera ssp sylvestris were more effective (up to 50%) against B. cinerea rather than those isolated from V. vinifera ssp vinifera. Six strains, all isolated from wild vines, belonging to four species (Meyerozyma guilliermondii, Hanseniaspora uvarum, Hanseniaspora clermontiae, and Pichia kluyveri) revealed one or more phenotypical characteristics associated to the analyzed modes of antagonistic action.